2017
DOI: 10.1002/polb.24558
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring 3D hydrogel systems for neuronal encapsulation in living electrodes

Abstract: State‐of‐the‐art neurorprostheses rely on stiff metallic electrodes to communicate with neural tissues. It was envisioned that a soft, organic electrode coating embedded with functional neural cells will enhance electrode‐tissue integration. To enable such a device, it is necessary to produce a cell scaffold with mechanical properties matched to native neural tissue. A degradable poly(vinyl alcohol) (PVA) hydrogel was tailored to have a range of compressive moduli through variation in macromer composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 88 publications
1
25
0
Order By: Relevance
“…In particular, the PVA-Tyr system allows covalent crosslinking with unmodified sericin and gelatin (PVA-SG) to respectively protect cells from the initial polymerization process and present cells with initial attachment cues. Previous research by Aregueta-Robles et al [32] has shown that PVA-SG can be tailored into polymeric scaffold variants that present SCs with a compressive modulus (K) from 2 kPa to 16 kPa, which is comparable to literature reports of nerve tissue stiffness [6,33]. While it was demonstrated that SCs survived and remained viable following the initial polymerisation process, the cell growth and development into functional phenotypes was not examined.…”
Section: Graphical Abstractmentioning
confidence: 91%
See 1 more Smart Citation
“…In particular, the PVA-Tyr system allows covalent crosslinking with unmodified sericin and gelatin (PVA-SG) to respectively protect cells from the initial polymerization process and present cells with initial attachment cues. Previous research by Aregueta-Robles et al [32] has shown that PVA-SG can be tailored into polymeric scaffold variants that present SCs with a compressive modulus (K) from 2 kPa to 16 kPa, which is comparable to literature reports of nerve tissue stiffness [6,33]. While it was demonstrated that SCs survived and remained viable following the initial polymerisation process, the cell growth and development into functional phenotypes was not examined.…”
Section: Graphical Abstractmentioning
confidence: 91%
“…Two variations of PVA-SG were fabricated via changes on macromer content as previously described [32]. In brief, gelatin (1 wt%) from porcine skin, (…”
Section: Pva-sg Hydrogel Fabricationmentioning
confidence: 99%
“…Hydrogels have been employed as 3D constructs which mimic the natural mechanical and structural properties of soft tissue (Khetan and Burdick, 2009;Goding et al, 2019;Syed et al, 2020). A biosynthetic PVA-SG hydrogel construct was chosen as the platform for this study, as it can be tailored to improve outcomes for neural cell encapsulation, as shown in prior research (Goding et al, 2017;Aregueta-Robles et al, 2018). The key objective of this study was to develop an understanding of neural cellular response to hydrogel encapsulation, to inform the design of future hydrogel constructs for neural tissue engineering applications, with the end goal of a hydrogel carrier which enables the development of complex neural networks such as those observed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogel physical characterization was performed as described by Aregueta-Robles et al (2018). Immediately after photopolymerization, 3 samples per time point (0, 1, 3, 7, 10, 14, 21, 28 days) were weighed to determine their initial wet mass (m i ).…”
Section: Swelling Ratio and Mass Lossmentioning
confidence: 99%
See 1 more Smart Citation